Parâmetros genéticos para o perfil de ácidos graxos do longissimus thoracis de bovinos da raça Nelore terminados em confinamento - Aboujaoude, Carolyn [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The intramuscular fatty acid (FA) profile in beef is important for human health, as well as being responsible for meat flavor and juiciness. The total quantity of FAs in the Longissimus thoracis predicts palatability and is the main determinant of carcass value by international standards of meat quality. It has been known that the type of FA has a larger impact on health issues when compared to the total quantity of such. There is a lack of genetic parameter estimates for beef fatty acid profile in Bos indicus, since the zebu breeds are the predominant source of beef in tropical and sub-tropical regions. Therefore, the results obtained in the present study should support farmers and researchers in order to define selection criteria to improve the beef fatty acid composition in zebu cattle. The objective of this study is to estimate (co)variance components and genetic parameters for beef FA composition in 937 Nellore bulls, previously kept in feedlot for a 90 day period with an average of 24 months of age and 500-550kg of slaughter weight. The FA profile was analyzed in Longissimus thoracis samples using a gas chromatography. The contemporary groups were organized based on farm and year of birth, and management group at yearling. The following 14 fatty acids were quantified: palmitic (C16:0), stearic (C18:0), oleic (C18:1 cis-9), linoleic (C18:2 cis-6), CLA (C18:2 cis-9 trans-11), CLA (C18:2 trans-10 cis-12), α-linolenic (C18:3 n3), myristic (C14:0), myristoleic (C14:1), elaidic (C18:1 n9t), vaccenic (18:1 t11), eicosatrienoic (C20:3 n6 cis-8,11,14), eicosatrienoic (C20:3 n3 cis-11,14,17) and arachidonic (C20:4). The proportion of saturated (SFA), monounsaturated (MUFA), polyunsaturated (PUFA), n-9, n-6 and n-3 were calculated using the individual fatty acid concentration. The model used for the (co) variance estimation included direct random genetic effect, the fixed effect of the CG, and the animal's slaughter age as a covariable ...

O perfil de ácidos graxos (AG) intramuscular da carne é importante para a saúde humana, além de ser responsável pelo sabor e suculência da carne. A quantidade total de AGs no Longissimus thoracis é um preditor de palatabilidade e o principal determinante do valor da carcaça de acordo com os padrões internacionais de qualidade da carne. Sabe-se que o tipo de AG tem um impacto maior sobre questões de saúde quando comparado com a quantidade total. Há uma falta de estimativas de parâmetros genéticos para perfil de ácidos graxos da carne em Bos indicus, uma vez que as raças zebuínas são a fonte predominante de carne bovina em regiões tropicais e sub-tropicais. Portanto, os resultados obtidos no presente estudo deve apoiar os agricultores e pesquisadores, a fim de definir critérios de seleção para melhorar a composição de ácidos graxos da carne de gado zebu. Objetivou-se com este estudo estimar componentes de (co)variância e parâmetros genéticos para composição de AG na carne de 937 touros Nelore terminados em confinamento por um período de 90 dias, com idade média de 24 meses e peso de abate entre 500-550kg. Os AG foram analisados no Longissimus thoracis e quantificados por cromatografia gasosa. Os grupos contemporâneos foram organizados de acordo com fazenda de nascimento, safra, e grupo de manejo ao sobreano. Os 14 ácidos graxos seguintes foram quantificados: palmítico (C16:0), esteárico (C18:0), oleico (C18:1 cis-9), linoleico (C18:2 cis-6), CLA (C18:2 cis-9 trans-11), CLA (C18:2 trans-10 cis-12), linolênico (C18:3 n3), miristico (C14:0), miristoleico (C14:1), elaidico (C18:1 n9t), vacênico (18:1 t11), eicosatrienoico (C20:3 n6 cis-8,11,14), eicosatrienoico (C20:3 n3 cis-11,14,17) e araquidônico (C20:4). As proporções dos AG saturados (AGS), monoinsaturados (AGMI), poli-insaturados (AGPI), n-9, n-6 e n-3 foram calculados usando as concentrações dos AG individuais. O modelo utilizado para a estimação...
Keywords: Bovino de corte; Nelore (Zebu); Estimativa de parametro; Acidos graxos; Confinamento (Animais); Genetica animal; Animal genetics